Mobiel Tentoonstellingsproject UNITS 98/99 : Kunst In Huis. - Coenjaerts, Raf; CC De Schakel, Waregem CC, Hasselt St.-Pietersabdij, Gent CC Ter Dilft, Bornem CC De Spil, Roeselare CC Zwaneberg, Heist op den Berg CC 't Vondel, Halle CC de Warande, Turnhout (Brussel : Kunst In Huis, 1998)
Clinckx, Christine ; De Gendt, Greta ; Denys, Ward ; Huyghe, Thomas ; Paelinck, Lieven ; Verhaegen, Hans
UNITS, CC de Schakel, Waregem, 9/2 - 1/3/98
UNITS, CC, Hasselt, 7/3 - 5/4/98
UNITS, St. - Pietersabdij, Gent, 31/10 - 29/11/98
UNITS, CC Ter Dilft, Bornem, 9/1 - 31/1/99
UNITS, CC De Spil, Roeselare, 6/2 - 7/3/99
UNITS, CC Zwaneberg, Heist op den Berg, 12/3 - 31/3/99